Efektivitas Program Komik Bicara Dalam Meningkatkan Pengetahuan dan Sikap Pencegahan Pelecehan Seksual Pada Remaja Tunanetra : Indonesia - adha, Yanuar Laely Lu'luatul; Rahmah, Suqya; Mawardiningih, Eka; Putra, Mohamad Delon Akase; Arifin, Alfin Irfan; Hidayah, Mudita Sri (UII, 2026)
The high incidence of sexual violence against visually impaired individuals, particularly in the Special Region of Yogyakarta (26 documented cases), underscores the urgency of providing self-protection education to this vulnerable group. The partner institution, MTs LB/A Yaketunis, faces challenges due to students' minimal understanding of physical interaction boundaries and the lack of adaptive educational media. This community service project aimed to analyze the effectiveness of multisensory media in enhancing the knowledge, attitudes, and protective skills of visually impaired adolescents regarding sexual harassment prevention. The intervention involved the development and implementation of a Braille Comic with Audio Narrative called